2013
DOI: 10.2298/jsc121106016b
|View full text |Cite
|
Sign up to set email alerts
|

Heavy metals content in Serbian old plum brandies

Abstract: Seven elements, namely, arsenic, lead, cadmium, copper, zinc, iron and manganese were determined in 31 samples of Serbian plum brandies by applying atomic spectrometry techniques. Flame atomic absorption spectrometry was used for quantification of copper, iron, zinc, manganese, lead and cadmium; and hydride generation atomic spectrometry absorption for arsenic quantification. Measured concentrations of heavy metals and arsenic was assessed according to the Serbian regulations, official regulations of som… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
45
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(55 citation statements)
references
References 25 publications
8
45
1
Order By: Relevance
“…GFAAS is a common technique for quantitative analysis of metals in various samples, including brandies too (Cameán et al 2001;Bonić et al 2013). This technique allows direct determination of a very small volumes or masses of samples, with high sensitivity and high S/N ratios, primarily because there are no flame gases to dilute the atoms that are analyzed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…GFAAS is a common technique for quantitative analysis of metals in various samples, including brandies too (Cameán et al 2001;Bonić et al 2013). This technique allows direct determination of a very small volumes or masses of samples, with high sensitivity and high S/N ratios, primarily because there are no flame gases to dilute the atoms that are analyzed.…”
Section: Introductionmentioning
confidence: 99%
“…Although Macedonian regulations control several parameters associated to the quality of alcoholic beverages such as methanol, aldehydes, esters, alcohols, total acidity, extract, and furfurol (Official Gazette of Republic of Macedonia 2010) and metals such as Cu, Fe, Zn, Pb, and Sn (Official Gazette of SRM 1980), large quantities of brandies produced under domestic conditions are sold on the market without any quality control. The concentration of metals in beverages produced in various countries has been the subject of many studies (Mena et al 1997;Capote et al 1999;Cvetković et al 2002;Soufleros et al 2004;Jurado et al 2007;Barciela et al 2008;Ivanova-Petropulos et al 2013;Bonić et al 2013;Ly et al 2013;Rodríguez-Solana et al 2014;Froes-Silva et al 2015), but to the best of our knowledge, such data are not readily available for brandy samples from Republic of Macedonia.…”
Section: Introductionmentioning
confidence: 99%
“…A comparative sensory evaluation and GC-MS analysis were performed on the Polish plum spirit (i.e., Śliwowica Łącka), Slovakian Pravá Bošacka Slivovica and Romanian Tzuica z Clej-Napoca [4]. Fruit spirits produced from Serbian plums were also analyzed [7][8][9]. The Serbian plum spirits were studied in order to, inter alia, determine the content of volatile compounds in different kinds.…”
Section: Introductionmentioning
confidence: 99%
“…The composition of four plum spirits, i.e., Manastrila from Belgrade, homemade Sokolova rakija, Karanka from the Užice region and Valjevka from the Valjevko region, was analyzed and compared by means of GC-FID and sensory analysis [7]. The Serbian plum spirits were also analyzed for the presence of Cu, Fe, Zn, Mn, Ca, Se and As using atomic absorption technique [9]. It was demonstrated that the composition of plum spirits is influenced by their geographical origin, preliminary processing, and the type and time of storage of the fruits [3,4,7,9,10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation